Lymph node regression and survival following neoadjuvant chemotherapy in oesophageal adenocarcinoma. Issue 12 (26th July 2018) - Davies, A R; Myoteri, D; Zylstra, J; Baker, C R; Wulaningsih, W; Van Hemelrijck, M; Maisey, N; Allum, W H; Smyth, E; Gossage, J A; Lagergren, J; Cunningham, D; et al.
Abstract: Background: The aim was to define the pathological response in lymph nodes following neoadjuvant chemotherapy for oesophageal adenocarcinoma and to quantify any associated survival benefit. Methods: Lymph nodes retrieved at oesophagectomy were examined retrospectively by two pathologists for evidence of a response to chemotherapy. Patients were classified as lymph node-negative (either negative nodes with no evidence of previous tumour involvement or negative with evidence of complete regression) or positive (allocated a lymph node regression score based on the proportion of fibrosis to residual tumour). Lymph node responders (score 1, complete response; 2, less than 10 per cent remaining tumour; 3, 10–50 per cent remaining tumour) and non-responders (score 4, more than 50 per cent viable tumour; 5, no response) were compared in survival analyses using Kaplan–Meier and Cox regression analysis. Results: Among 377 patients, 256 had neoadjuvant chemotherapy. Overall, 68 of 256 patients (26·6 per cent) had a lymph node response and 115 (44·9 per cent) did not. The remaining 73 patients (28·5 per cent) had negative lymph nodes with no evidence of regression. Some patients had a lymph node response in the absence of a response in the primary tumour (27 of 99, 27 per cent). Lymph node responders had a significant survival benefit ( P < 0·001), even when stratified by patients with or without a response in the primary tumour. On multivariable analysis, lymph node responders had decreased overall (hazard ratio 0·53, 95 per cent c.i. 0·36 to 0·78) and disease-specific (HR 0·42, 0·27 to 0·66) mortality, and experienced reduced local and systemic recurrence. Conclusion: Lymph node regression is a strong prognostic factor and may be more important than response in the primary tumour. Abstract : Nodal response predicts survival